THE INFLUENCE OF PRINCIPAL ENTREPRENEUR LEADERSHIP AND ORGANIZATIONAL CULTURE ON THE CREATIVITY OF TEACHERS - Afrah Khaiyati ORBANI; Ihsana El KHULUQO (Journal of Education and Leadership in Education, 2022)
This research aims to reveal and to study the influence of the principal entrepreneur leadership and organizational culture toward teacher creativity in the Tourism Vocational High Schools in Southern Jakarta. This research is one that is quantitative survey-based employing questionnaires and path analysis. Study population consists of all 226 teachers in those schools, applying Slovin’s formula with sampled teachers amounting 144, and extra 30 teachers trial pre sampled teachers. Method applied in this research is Simple Random Sampling.This research has hypothesis, as follow: (1) there is direct positive influence of the principal entrepreneur leadership toward teacher creativity, (2) there is direct positive influence of the organizational culture toward teacher creativity, and (3) there is direct positive influence of the principal entrepreneur leadership toward organizational culture. Trial instrument is applied to obtain both validity of the statements provided and realibility of the instrument at the same time by using formula provided by Pearson Product Moment and reliabilities calculated by Alpha Cronbach formulation, and every instrument indicated that reliabilities of; teacher’s creativity rii=0.886, principal entrepreneur leadership rii= 0.893 and organization culture rii= 0.909.Furthermore, the big of its influences measured by path analysis formulation for significance level α = 0,05, The result is concluded, zero hypothesis (H0), explained there is not direct positive influence of the principal entrepreneur leadership and organizational culture toward teacher creativity is rejected, while alternative hypothesis (H1), explained there is direct positive influence of the principal entrepreneur leadership and organizational culture toward teacher creativity is accepted.